Discourses of democratic education in the preparation of teachers for international contexts: an analysis of curriculum documents - Helland, Karianne (Nordic Journal of Comparative and International Education (NJCIE), 2023)
This article offers a critical and comparative view of democratic education as expressed in curriculum documents of ten teacher education programmes aimed at educating teachers for international contexts. Democracy and democratic education are concepts with contested meanings, and I use the discourses of democratic education identified by Sant (2019) as an analytical tool for mapping the understandings or approaches present in the documents. Intercultural competence, global citizenship, and International Mindedness are contested and overlapping concepts which intersect with these democratic discourses. The tension between a neoliberal discourse and a traditional focus on international-mindedness and global citizenship is often described as characteristic of international schools. The “internationalist” ethos dominates course descriptions and learning objectives. While several discourses of democratic education are present, the focus is mainly individual and geared towards intercultural understanding rather than democratic competences. The idea of the student as a citizen beyond the limits of the classroom walls is not very visible, nor are concepts of power and privilege.